The complete genome sequence of the cold adapted crude-oil degrader: Pedobacter steynii DX4 - Sijing Chang; Gaosen Zhang; Ximing Chen; Haozhi Long; Yilin Wang; Tuo Chen; Guangxiu Liu (Standards in Genomic Sciences, 2017)
Abstract Pedobacter steynii DX4 was isolated from the soil of Tibetan Plateau and it can use crude oil as sole carbon and energy source at 15 °C. The genome of Pedobacter steynii DX4 has been sequenced and served as basis for analysis its metabolic mechanism. It is the first genome of crude oil degrading strain in Pedobacter genus. The 6.58 Mb genome has an average G + C content of 41.31% and encodes 5464 genes. In addition, annotation revealed that Pedobacter steynii DX4 has cold shock proteins, abundant response regulators for cell motility, and enzymes involved in energy conversion and fatty acid metabolism. The genomic characteristics could provide information for further study of oil-degrading microbes for recovery of crude oil polluted environment.